GNSS signal reflections off sea ice - Eleftherios Christos, Drosinos (Chalmers tekniska högskola / Institutionen för rymd- och geovetenskap, 2016)
Multipath has a deleterious effect on GNSS positioning applications, but on the other hand is extremely beneficial to reflectometry, a field of science that is of utmost importance nowadays. Using GPS and/or GLONASS signals for low elevation angles, one can take advantage of this effect. Direct and reflected GNSS signals interfere with each other to form multipath signals, the composite SNR of which is recorded by a GNSS antenna connected to a receiver. While the satellites move across the sky, an interference pattern can be observed, which for low elevation angles can be very useful and one can calculate the reflector’s height (distance between the antenna phase centre and the reflection surface). In this thesis, the SNR analysis technique was used to isolate the amplitude and the damping factor of dSNR in order to draw conclusions about the sea-surface conditions under freeze states in the vicinity of the GNSS-R station installed in Onsala Space Observatory. It is shown that the damping factor is more sensitive to reflected signals, than the amplitude and thus can indicate whether there is ice or not near a GNSS-R tide gauge.